2011
DOI: 10.1095/biolreprod.110.086686
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Programming: Impact of Excess Prenatal Testosterone on Intrauterine Fetal Endocrine Milieu and Growth in Sheep1

Abstract: Prenatal testosterone excess in sheep leads to reproductive and metabolic disruptions that mimic those seen in women with polycystic ovary syndrome. Comparison of prenatal testosterone-treated sheep with prenatal dihydrotestosterone-treated sheep suggests facilitation of defects by androgenic as well as androgen-independent effects of testosterone. We hypothesized that the disruptive impact of prenatal testosterone on adult pathology may partially depend on its conversion to estrogen and consequent changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
99
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 77 publications
(112 reference statements)
6
99
0
2
Order By: Relevance
“…Administration of testosterone during pregnancy in rats or sheep does not affect the food intake or weight gain of the dam or the maternal levels of insulin, estrogen, progesterone, glucose, or lipids (36,47). These findings indicate that the effects of prenatal androgenization on the placenta, fetus, and female offspring are not caused by changes in maternal metabolism.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Administration of testosterone during pregnancy in rats or sheep does not affect the food intake or weight gain of the dam or the maternal levels of insulin, estrogen, progesterone, glucose, or lipids (36,47). These findings indicate that the effects of prenatal androgenization on the placenta, fetus, and female offspring are not caused by changes in maternal metabolism.…”
mentioning
confidence: 80%
“…Testosterone is a lipophilic hormone and can diffuse from the amniotic fluid into the fetal circulation and across the placenta (16,28,44). However, previous studies have reported that a significant increase in maternal testosterone level in rats is not associated with a significant increase in testosterone in the fetus (35,50), whereas in both sheep and monkeys it has been shown that elevated maternal testosterone levels also elevate fetal testosterone levels in female offspring (2,47). Also, a recent preliminary report indicates altered enzymatic regulation in PCOS placentas, as demonstrated by higher 3␤-HSD1 placental expression and lower P450 aromatase activities compared with controls (11).…”
Section: Effect Of Prenatal Testosterone Exposure On the Placenta Andmentioning
confidence: 99%
“…In support of this premise, placentas from PCOS mothers were found to have lower aromatase and higher 3b-HSD1 activities, which could lead to increased androgen levels during pregnancy (Maliqueo et al 2013). The studies of Veiga-Lopez et al (2011) in sheep have found male and female sheep fetuses whose mothers were administered testosterone to have elevated plasma testosterone levels compared with their control counterparts.…”
Section: Effect Of Prenatal Testosterone Excess On Gonadal Testosteromentioning
confidence: 93%
“…3,27 In sheep, abnormalities of the reproductive, metabolic, and growth axes can be induced by exposure to abnormal steroid concentrations or environmental endocrine disrupters during vulnerable stages of in utero development. 11,18,19,21,23,34 Prenatal exposure to excess androgens between days 30 and 90 of gestation has a virilizing effect on the external genitalia of female lambs, and affected animals have a penis and a scrotal sac without testes. 4,14 The ovaries are in the correct anatomical position but have gross abnormalities soon after birth.…”
Section: 26mentioning
confidence: 99%